THE IMPORTANCE OF MODERN PEDAGOGICAL TECHNOLOGIES TO CORRECT THE SPEECH OF PRESCHOOLERS - Normatova, Maftuna (Журнал Педагогики и психологии в современном образовании, 2021)
The aim of the present article is to discuss the conditions for effective development of coherent descriptive speech in preschool children with speech underdevelopment problems.